2007
DOI: 10.1074/jbc.m610176200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Influx and Mitochondrial Alterations at Synapses Exposed to Snake Neurotoxins or Their Phospholipid Hydrolysis Products

Abstract: Snake presynaptic phospholipase A2 neurotoxins (SPANs) bind to the presynaptic membrane and hydrolyze phosphatidylcholine with generation of lysophosphatidylcholine (LysoPC) and fatty acid (FA). The LysoPC ؉ FA mixture promotes membrane fusion, inducing the exocytosis of the ready-to-release synaptic vesicles. However, also the reserve pool of synaptic vesicles disappears from nerve terminals intoxicated with SPAN or LysoPC ؉ FA. Here, we show that LysoPC ؉ FA and SPANs cause a large influx of extracellular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 42 publications
(49 reference statements)
3
48
0
Order By: Relevance
“…However, if their hydrolytic activity is concentrated on defined organelles, even minor local phospholipid hydrolysis may be sufficient to alter dramatically the organelle physiology. This consideration would be particularly relevant for mitochondria, which does interact with SPANs and are affected in their membrane permeability properties (Scorrano et al 2001;Rigoni et al 2007). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if their hydrolytic activity is concentrated on defined organelles, even minor local phospholipid hydrolysis may be sufficient to alter dramatically the organelle physiology. This consideration would be particularly relevant for mitochondria, which does interact with SPANs and are affected in their membrane permeability properties (Scorrano et al 2001;Rigoni et al 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, glial cells and neurons will have distinct and different compositions of membrane lipid, which will further complicate the MS analysis. CGN neurons are highly sensitive to SPANs and develop a well-defined bulging at axon and dendrite terminals within few minutes from toxin addition; such morphological alteration is accompanied by cytosolic calcium increase at nerve terminals and glutamate release from neurons (Rigoni et al 2004(Rigoni et al , 2007. These effects are mimicked by the addition of an equimolar mixture of the PLA 2 hydrolysis products, lysophosphatidylcholine (LysoPC) + oleic acid, indicating that these molecules are the biochemical mediators of SPAN action (Rigoni et al 2005;Caccin et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As SPANs require Ca 2ϩ for their hydrolytic activity, the biological relevance of these findings was considered to be questionable. However, we recently documented that SPANs do induce the accumulation of Ca 2ϩ within nerve terminals (7), and this finding reopened the possibility of a contribution of the entry of SPANs in the nerve terminal cytosol to the pathogenesis of envenomation.…”
mentioning
confidence: 92%
“…It was also shown that an early consequence of the action of SPANs is the hydrolysis of phosphatidylcholine into lysophosphatidylcholine and fatty acids and that their equimolar mixture mimics the swelling response of nerve terminals to the toxin itself (6). The SPAN-induced nerve bulges accumulate Ca 2ϩ , and, this event is accompanied by mitochondrial rounding and depolarization (7). The cytosolic [Ca 2ϩ ] increase could also trigger the activity of many Ca 2ϩ -activated hydrolases of nucleic acids, proteins, and lipids, all factors that could account for the pronounced degeneration of nerve terminals poisoned by SPANs (8 -11).…”
mentioning
confidence: 99%